Strontium and magnesium ions released from bioactive titanium metal promote early bone bonding in a rabbit implant model. (November 2017) - Okuzu, Yaichiro; Fujibayashi, Shunsuke; Yamaguchi, Seiji; Yamamoto, Koji; Shimizu, Takayoshi; Sono, Takashi; Goto, Koji; Otsuki, Bungo; Matsushita, Tomiharu; Kokubo, Tadashi; Matsuda, Shuichi
Graphical abstract: Abstract: We have previously developed the "alkali and heat treatment" method to confer bioactivity (bone-bonding ability) to titanium metal (Ti). As strontium (Sr) and magnesium (Mg) ions reportedly promote osteoblastic cell proliferation and differentiation and accelerate bone formation, we improved this method to induce the release of Sr (Sr-Ti) or Mg (Mg-Ti) ions from Ti in a previous study. Here, we evaluated the bioactivity of these novel surface treatments, Sr-Ti and Mg-Ti. In vitro evaluation of cell viability, expression of integrin β1, β catenin, and cyclin D1, osteogenic gene expression, alkaline phosphatase activity, and extracellular mineralization using MC3T3-E1 cells revealed that Sr-Ti and Mg-Ti enhanced proliferation and osteogenic differentiation. In rabbit in vivo studies, Sr-Ti and Mg-Ti also provided greater biomechanical strength and bone-implant contact than the positive control Ti (Ca-Ti), especially at the early stage (4–8 weeks), and maintained these properties for a longer period (16–24 weeks). Advantages of the improved method include process simplicity, applicability for any implant shape, and lack of adverse effects on implant composition and structure. Therefore, our treatment is promising for clinical applications to achieve early bone bonding. Statement of Significance: Implantation into osteoporotic bone constitutes a challenging problem because of early migration or loosening of the implant, which is primarily due to insufficient initial fixation in porotic bone. Therefore, it is desirable to provide implants with a capacity for early bone bonding. We have achieved conferring early bone bonding ability to titanium metal by releasing strontium ions or magnesium ions. Our treatment is promising for clinical applications to achieve early bone bonding of orthopedic or dental Ti-based implants.